2022
DOI: 10.4103/ajps.ajps_167_20
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Exstrophy

Abstract: Introduction: Bladder exstrophy is a major malformation in paediatric urology. The treatment results are not still completely satisfactory, and their management is an enormous problem in Sub-Saharan Africa. While outlining our challenges, we report our management experience to improve our results. Subjects and Methods: We retrospectively reviewed the records of patients undergoing surgical repair of classic bladder exstrophy at our department between January 2010 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The majority of patients (75%) in the current study ingested alkaline caustic agents, this was in accordance with several studied, which proposed that acidic agents usually cause severe immediate pain after ingestion and are rapidly expelled, while alkaline agents have almost imperceptible taste and odor with an easy swallowing, in addition to the wide spread and availability of alkaline agents in homes (Agbara et al, 2019;Acehan et al, 2021). Nevertheless, no significant 2020) reported that alkalis ingestion was associated with higher incidence of complications, higher probability of esophageal stricture and worse endoscopic score compared to acids.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of patients (75%) in the current study ingested alkaline caustic agents, this was in accordance with several studied, which proposed that acidic agents usually cause severe immediate pain after ingestion and are rapidly expelled, while alkaline agents have almost imperceptible taste and odor with an easy swallowing, in addition to the wide spread and availability of alkaline agents in homes (Agbara et al, 2019;Acehan et al, 2021). Nevertheless, no significant 2020) reported that alkalis ingestion was associated with higher incidence of complications, higher probability of esophageal stricture and worse endoscopic score compared to acids.…”
Section: Discussionsupporting
confidence: 90%